ENHANCING STATISTICAL LITERACY AND INVESTMENT LITERACY THROUGH THE LOVE STATISTICS VILLAGE PROGRAM (KELURAHAN CANTIK) IN PADANG HULU DISTRICT, TEBING TINGGI CITY - Willy Cahyadi; Didik Gunawan; Yenni Arfah; Dedy Dwi Arseto; Aisyah Siregar; Augustama Sabam Pasaribu; Elina Maisyarah; Andika; Muhammad Fahrezi Agesi; Yula Anggi Kristiani; Muhammad Ridho Akbar Lubis (RADJA PUBLIKA, 2026)
The Kelurahan Cantik (Love Statistics Urban Village) Program is an initiative of the Central Statistics Agency (Badan Pusat Statistik/BPS) aimed at enhancing the capacity of urban village officials in managing statistical data as a foundation for evidence-based development planning and policymaking. At the same time, the relatively low levels of financial and investment literacy among the community remain significant challenges that require continuous educational efforts. Therefore, this Community Service Program (Pengabdian kepada Masyarakat/PKM) was conducted to improve the statistical literacy of urban village officials and enhance public understanding of financial and investment literacy through collaboration among STIE Bina Karya, the Central Statistics Agency (BPS) of Tebing Tinggi City, and the Indonesia Stock Exchange (IDX). The program was implemented on July 14, 2026, at the Padang Hulu District Office Hall, Tebing Tinggi City, involving district officials, urban village officials, statistical agents, Statistics Corner (Pojok Statistik) ambassadors, and community representatives from Pabatu, Padang Merbau, and Tualang Urban Villages. The implementation methods included preparation, socialization, lectures, technical training, mentoring, statistical data presentation practices, interactive discussions, and activity evaluation. The results demonstrated that participants gained a better understanding of statistical data management and presentation techniques, recognized the importance of utilizing data as a basis for development planning, and improved their knowledge of the capital market, legal investment instruments, investment benefits, and investment risks. Overall, the program successfully strengthened collaboration among higher education institutions, government agencies, and financial institutions in promoting data-driven community empowerment.